ANALISIS FAKTOR – FAKTOR YANG MEMPENGARUHI AUDIT JUDGEMENT PADA PERUSAHAAN KONSULTAN BISNIS KECIL DI TANGERANG - Priscillia Sharon (Sekolah Tinggi Ilmu Ekonomi Wiyatamandala, 2017)
Audit Judgement is one of important aspect in Accounting Consulting Business. Audit Judgement create expectation and trust between corporate and reader of Financial Report. It is really important to understand the flow and how Audit Judgement can be derived. Purpose of this research is to “revisit” all possible factor that could affect audit judgement in small and new business consultant firm in Tangerang. The author aim to understand more about audit judgement and hope could find same factor in small firm case. Finding of this research confirm that there is influence of audit experience and pressure toward obedience. This research use F test, t test and R2 to valuate research model. Pressure toward obedience has negative relationship with audit judgement. Researcher conclude that in small firm case, most of high level executive try their best to conduct ethical behavior and make sure they can perform best services for their clients. While in lower level, most of junior still obey their leader or their clients. But sometimes it caused confusion because the clients objective not always the same as the top executive objective. So in the end, the top level could maintain their standard and researcher suggest they could create standard code of conduct in their office, so at junior level, they could learn be more professional base on ethical behavior.